Psikoedukasi Untuk Mencegah Burnout Pegawai di Dinas Perhubungan Provinsi Sumatera Selatan - Desy Arisandy; Rizka Yuniarsa (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2026)
This psychoeducation activity aims to prevent the risk of burnout in Subdivision employees South Sumatra Provincial Transportation Service Finance. The method used is observation and Distribution of pre and post education questionnaires with a quantitative descriptive approach. Material Delivered through presentations, short videos, and ice breaking sessions. The result shows the existence of Tendency of emotional fatigue and decreased work spirit in some participants before Education. After the activity, there is an increase in understanding about burnout and a simple way to Managing work stress. This psychoeducation shows the potential as a first step in supporting Mental health in the workplace.